Improving Negative First Routing Algorithm with Load Equalization of Virtual Channel in NoC - Tao He; Xingming Zhang; Tao Qin (Institute of Advanced Engineering and Science, 2013)
This article study chip communication mechanisms deeply based on the NoC (Network on Chip) technology and a load equalization of virtual channel (LEVC) routing algorithm for Torus networks is proposed, which splits the physical network into virtual networks in the case of physical link load equalization. According to the predefined rules, packets use different virtual networks on their way to destinations and network achieve no deadlock, no livelock purpose. The algorithm study load equalization on the level of virtual channel by introducing the random factor. Simulation results show that compared with the negative first for Torus networks algorithm, the network performance can be dramatically improved for different traffic pattern by selecting a specific value of the random parameter respectively. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3483